The influence of assessment on learning motivation - Efremova Nadezhda; Shvedova Svetlana; Huseynova Anastasia (SHS Web of Conferences, 2019)
This paper considers methodological approaches to the assessment of learning achievement, analysing the impact of the mark on learning motivation of students. External testing and subsequent questionnaires data may serve as an indicator of increasing learning motivation of students due to their confidence in the assessment results. Reliability of assessment is an incentive to enhance learning activities of students and increase interest in a given academic discipline. We observed difficulties of obtaining an objective assessment in schools and possible ways of overcoming them. The research provides the basic provisions of the assessment using the design pattern of assessment tools and processes on the basis of evidence-based arguments modelled on Evidence Centered Design which provides assistance in the development of high-quality assessment tools. The use of patterns may allow educators to make greater use of methods for classifying, organising and planning the assessment of cognitive and competency-based learning outcomes.